Clinician's Attitudes to the Introduction of Routine Weighing in Pregnancy - Tim Hasted; Helen Stapleton; Michael M. Beckmann; Shelley A. Wilkinson (Hindawi Limited, 2016)
Background. Excessive gestational weight gain poses significant short- and long-term health risks to both mother and baby. Professional bodies and health services increasingly recommend greater attention be paid to weight gain in pregnancy. A large Australian tertiary maternity hospital plans to facilitate the (re)introduction of routine weighing of all women at every antenatal visit. Objective. To identify clinicians' perspectives of barriers and enablers to routinely weighing pregnant women and variations in current practice, knowledge, and attitudes between different staff groups. Method. Forty-four maternity staff from three professional groups were interviewed in four focus groups. Staff included midwives; medical staff; and dietitians. Transcripts underwent qualitative content analysis to identify and examine barriers and enablers to the routine weighing of women throughout pregnancy. Results. While most staff supported routine weighing, various concerns were raised. Issues included access to resources and staff; the ability to provide appropriate counselling and evidence-based interventions; and the impact of weighing on patients and the therapeutic relationship. Conclusion. Many clinicians supported the practice of routine weighing in pregnancy, but barriers were also identified. Implementation strategies will be tailored to the discrete professional groups and will address identified gaps in knowledge, resources, and clinician skills and confidence.